Central nervous system-derived cells express a kappa B-binding activity that enhances human immunodeficiency virus type 1 transcription in vitro and facilitates TAR-independent transactivation by Tat. - Taylor, J P (1994)
The Tat protein of human immunodeficiency virus type 1 (HIV-1) is a potent activator of long terminal repeat-directed transcription. While in most cell types, activation requires interaction of Tat with the unusual transcription element TAR, astrocytic glial cells support TAR-independent transactivation of HIV-1 transcription by Tat. This alternative pathway of Tat activation is mediated by the viral enhancer, a kappa B domain capable of binding the prototypical form of the transcription factor nuclear factor kappa B (NF-kappa B) present in many cell types, including T lymphocytes. Tat transactivation mediated by the kappa B domain is sufficient to allow replication of TAR-deleted mutant HIV-1 in astrocytes. The present study demonstrates the existence of kappa B-specific binding factors present in human glial astrocytes that differ from prototypical NF-kappa B. The novel astrocyte-derived kappa B-binding activity is retained on an HIV-1 Tat affinity column, while prototypical NF-kappa B from Jurkat T cells is not. In vitro transcription studies demonstrate that astrocyte-derived kappa B-binding factors activate transcription of the HIV-1 long terminal repeat and that this activation is dependent on the kappa B domain. Moreover, TAR-independent transactivation of HIV-1 transcription is reproduced in vitro in an astrocyte factor-dependent manner which correlates with kappa B-binding activity. The importance of the central nervous system-enriched kappa B transcription factor in the regulation of HIV-1 expression is discussed.